Forms of avian reovirus in poultry production: An overview - Abd El-Ghany, Wafaa (Journal of Advanced Veterinary Research, 2024)
This review article focuses on avian reovirus (ARV) regarding the virus characters, susceptibility and transmission, the different clinical forms, laboratory diagnosis, and preventive measures. Despite most of ARV strains are abundant and innocuous, they are responsible for many diseases conditions in poultry industry. The pathogenic ARV strains induce great economic losses including growth retardation, increasing culling rate, high mortality rate, immunosuppression, and increasing the carcass rejection rate at processing. Strains of ARV belong to the family Reoviridae and genus Orthoreovirus are non-enveloped and double-stranded RNA. Almost all of avian species are susceptible to infection especially at young ages. The virus rapidly spreads among flocks via the horizontal, vertical, and mechanical routes. The infection with ARV is mainly associated with arthritis/ tenosynovitis and runting stunting syndrome. However, other clinical pictures such as gastroenteritis, hepatitis, myocarditis, and respiratory disease are also related to ARV infections. Laboratory diagnosis is based on isolation and characterization of the virus using conventional methods of detection. Nevertheless, recent molecular techniques are also regarded as suitable for the efficient diagnosis. Serological detection of specific ARV antibodies have been also applied. Adoption of hygienic measures and vaccination with live or inactivated vaccines are the most suitable methods for the prevention of field ARV infections.